Transmedia storytelling: expanding formatted contents in global - Yoon, Hyeyung (Frontiers in Communication, 2025)
Currently, many entertainment contents around the world are going through transmedia. In particular, video contents that cross media have various changes and acceptance patterns. In addition to being converted into new texts in new media to reflect the differentiation of media, global contents are also reproduced as local contents in new regions. This appears in different ways depending on the genre, such as movies and series. In the case of TV shows, the original works are formatted and these formats are traded with overseas production companies to reproduce and broadcast new contents with modified formats in each region. In this trend, the following characteristics of transmedia storytelling were derived by analyzing cases of formatted contents that are popular worldwide. ① Reconstructing native language to help each country and ethnicity understand, ② Modifying the structure of texts to reflect local cultural backgrounds, ③ Reconstructing characters to reflect local trends, ④ Reflecting micro contents of local culture, ⑤ Reconstructing music, art, and various multimedia, ⑥ Developing communication platforms with viewers. Most format contents are reproduced as new contents through these processes. Currently, in the global entertainment market, all contents must devise strategies for developing global formats. The industry will be able to plan content more effectively and efficiently through the storytelling issues of formatted contents presented above. This article is designed as a narrative review focusing on storytelling and cultural contents in entertainment formats. By synthesizing academic perspectives and industry cases, it contributes to a deeper understanding of storytelling as a strategic framework in cultural content studies.